2010
DOI: 10.1021/la903569v
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Microarrays by Microcontact Printing

Abstract: This Article describes the preparation of carbohydrate microarrays by the immobilization of carbohydrates via microcontact printing (microCP) on glass and silicon substrates. To this end, diene-modified carbohydrates (galactose, glucose, mannose, lactose, and maltose) were printed on maleimide-terminated self-assembled monolayers (SAMs). A Diels-Alder reaction occurred exclusively in the contact area between stamp and substrate and resulted in a carbohydrate pattern on the substrate. It was found that cyclopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 47 publications
3
59
0
3
Order By: Relevance
“…Lectin carbohydrate interactions: As described in [34], in order to reduce non-specific protein adsorption, the arrays were incubated with a 3% bovine serum albumin (BSA) solution in PBS buffer (pH 7.5, 0.1% Tween 20) for 30 min and washed two times with PBS buffer prior to lectin screening. The surfaces of the carbohydrate arrays were covered by a solution of 1 mM FITC HisHis and 1 μg of labeled lectin (TRITC ConA or FITC PNA) in 100 μL of HEPES buffer (20 mM HEPES, pH 7.5, 0.15 M NaCl, 1.0 mM CaCl 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lectin carbohydrate interactions: As described in [34], in order to reduce non-specific protein adsorption, the arrays were incubated with a 3% bovine serum albumin (BSA) solution in PBS buffer (pH 7.5, 0.1% Tween 20) for 30 min and washed two times with PBS buffer prior to lectin screening. The surfaces of the carbohydrate arrays were covered by a solution of 1 mM FITC HisHis and 1 μg of labeled lectin (TRITC ConA or FITC PNA) in 100 μL of HEPES buffer (20 mM HEPES, pH 7.5, 0.15 M NaCl, 1.0 mM CaCl 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our group has shown that also simple carbohydrate microarrays can be conveniently prepared by μCP if reactive glycosides are printed on a suitable target self-assembled monolayer (SAM) [3132]. Amongst others, we reported carbohydrate microarrays fabricated by cycloaddition of alkynes on azide-terminated SAMs [33], by Diels–Alder reaction of cyclopentadienes and furans on maleimide-terminated SAMs [34], by thiol–ene click reaction of functionalized thiols on alkene-terminated SAMs [35] as well as by strain promoted cycloadditions on azide- and nitriloxide-terminated SAMs [36] using μCP. Homogenous spots, high-edge resolution, good reproducibility and short reaction times can be easily achieved by using µCP.…”
Section: Introductionmentioning
confidence: 99%
“…lCP is simple to apply and has good versatility [8,[19][20][21][22][23][24]. It was introduced by Kumar and coworkers in 1993 for replicating patterns generated by photolithography [25].…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication of fluorescence patterns is of great technological importance in a variety of fields including sensor, display and electronic industries. [1][2][3][4][5] Among the various techniques such as photoirradiation, [6][7][8][9] inkjet/screen printing, 10,11 vapor deposition, 12 and microcontact printing [13][14][15] methods developed to date, the photoirradiation method represents the most popular and practical approach for the fabrication of patterned fluorescence images on a solid support. In a typical photoirradiation method, functional molecules having photochemically removable protecting groups are immobilized or coated on the solid substrate.…”
mentioning
confidence: 99%